Timing and causes of death in acute myocardial infarction complicated by cardiogenic shock. (2nd May 2022) - Witten Davodian, L; Larsen, JKP; Povlsen, AL; Josiassen, J; Helgestad, OKL; Udesen, NLJ; Hassager, C; Schmidt, H; Kjaergaard, J; Holmvang, L; Jensen, LO; Ravn, HB; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The Danish Heart Foundation Odense University Hospital and Rigshospitalets Research Council. Background: Acute myocardial infarction complicated by cardiogenic shock (AMICS) comprises a heterogenous population with high mortality. Insight in timing and cause of death may improve understanding of the condition and aid individualization of treatment. Purpose: To determine the cause and timing of death in patients admitted with AMICS. Methods: This was a retrospective, multi-center observational cohort study based on 1716 AMICS patients treated during the period of 2010-2017, of whom 904 died prior to hospital discharge from either of two tertiary cardiac centers in Denmark providing advanced care for cardiogenic shock for 3.9 million inhabitants. Patients admitted with AMICS were identified through national registries and review of individual patient charts. Only patients dying during hospitalization were eligible. Cause of death was categorized as caused by progressive cardiac failure, multi organ failure or due to neurological damage. Time to death was calculated in hours from first medical contact to death. Results: Among 904 patients with AMICS who died prior to hospital discharge (median age 72 years [IQR: 63 - 79], 70% men), 342 (38%) patients had suffered an out-of-hospital cardiac arrest (OHCA). The most frequent cause of death was primary cardiac (54%), whereas 24% died of neurologic injury and 20% of multi-organ failure. Time to death was 13 hours [IQR: 5, 43] for cardiac failure; 140 hours [IQR: 95, 209] in neurological injury; and 137 hours [IQR: 59, 321] in multi-organ failure, p<0.001. The causes of death in patients presenting with OHCA were neurological injury in 57%, as opposed to 4% among patients not presenting with OHCA, p<0.001. No specific phenotype on admission characterized patients with OHCA who died from neurological injury or cardiac causes. Conclusion: In patients with AMICS, cause of death was mainly primary cardiac failure followed by neurological injury and multi-organ failure. Median time from first medical contact to death was only 13 hours in patients dying from cardiac causes. The risk of dying of neurological injury was low in patients without OHCA.